The Impact of Brand Equity towards Purchase Intention on PT. X’s Candy - Davin Suryadi (iBuss Management, 2015)
The purpose of this research is to discover the impact of brand equity towards customer’s purchase intention of PT. X’s candy product. Brand equity itself consists of brand loyalty, brand awareness, brand association, and perceived quality. By the end of this research, it will be discovered how brand equity impacts customer’s purchase intention simultaneously and how each element of brand equity impacts customer’s purchase intention.The sampling method in this research is simple random sampling with 102 respondents. The analysis technique for this research is multiple-linear regression, that can show how significant customer’s purchase intention is influenced by brand equity simultaneously or/and individually. In this research, it is shown that brand equity simultaneously influence customer’s purchase intention and brand association and perceived quality are the individual elements that influence customer’s purchase intention.